Wykluczenie emerytalne w III filarze - Dybał, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article is an attempt to assess pension exclusion in the third pillar of the pension system in Poland. Therefore, the subject of the research are elements that are part of the third retirement pillar in Poland — PPE, IKE, IKZE. The subject of the research is the analysis of pension exclusion in the third pillar of the Polish pension system. The following research questions have been raised: 1) What factors influence pension exclusion in the third pillar of the pension system in Poland? 2) Is there pension exclusion in the third pillar of the pension system in Poland?
Keywords: pension exclusion; third pillar; supplementary pension; PPE; IKE; IKZE; pension system